An adolescent with isolated systolic hypertension – case report and diagnostic and therapeutic approach - Bujanowicz, Adam; Szyszka, Michał; Skrzypczyk, Piotr (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Primary hypertension (PH) is the most common cause of arterial hypertension in adolescents; many of these patients present with isolated systolic hypertension (ISH). The study presents a case of a 16-year-old male adolescent with PH. The patient had ISH in both 24-hour-ambulatory and office measurements. Secondary causes and hypertension-mediated organ damage were excluded. Evaluation of the vascular phenotype revealed low central systolic blood pressure (109 mm Hg), high peripheral augmentation index (27 mm Hg), and high arterial elasticity. The boy was started on non-pharmacological treatment. The manuscript discusses up-to-date knowledge on the pathogenesis and evolution of ISH in young people. A diagnostic and therapeutic approach according to the European Society of Hypertension is presented. Adolescents with ISH require evaluation of the vascular phenotype. There is a need for further studies on the evolution and long-term outcome in young people with this form of arterial hypertension.